2014
DOI: 10.1042/bsr20140094
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of the water soluble Aβ17–34 peptide

Abstract: Alzheimer's disease is the most common neurodegenerative disorder in the world. Its most significant symptoms are memory loss and decrease in cognition. Alzheimer's disease is characterized by aggregation of two proteins in the brain namely Aβ (amyloid β) and tau. Recent evidence suggests that the interaction of soluble Aβ with nAChR (nicotinic acetylcholine receptors) contributes to disease progression. In this study, we determine the NMR structure of an Aβ17–34 peptide solubilized by the addition of two glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This observation is in agreement with a report based on a completely different simulation setup, where a similar intermediate with 3 10 -helical structure between residues 26 and 28 was sampled in Aβ21-30 41 . The final CPD-folded structure does not exhibit a well-defined α-helical structure prior to the kink (residues 19–26) (Fig 2B) but is within 3.42 Å (backbone RMSD) of the reference folded structure of Aβ17-34 (PDB ID 2MJ1) 40 . It is worth noting here that the reference folded structures from the NMR ensemble differ from one another by up to 2.79 Å.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This observation is in agreement with a report based on a completely different simulation setup, where a similar intermediate with 3 10 -helical structure between residues 26 and 28 was sampled in Aβ21-30 41 . The final CPD-folded structure does not exhibit a well-defined α-helical structure prior to the kink (residues 19–26) (Fig 2B) but is within 3.42 Å (backbone RMSD) of the reference folded structure of Aβ17-34 (PDB ID 2MJ1) 40 . It is worth noting here that the reference folded structures from the NMR ensemble differ from one another by up to 2.79 Å.…”
Section: Resultsmentioning
confidence: 95%
“…It is worth noting here that the reference folded structures from the NMR ensemble differ from one another by up to 2.79 Å. Moreover, in the NMR experiment, the Aβ17-34 contained two additional glutamic acid residues at each terminus, which increased solubility and stabilized the helical structure in aqueous solution 40 ; since our simulations only included residues 17–34 (i.e., without the terminal residues added to stabilize the helix), we consider that CPD achieved a satisfactory proportion of helical structure.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is pertinent to compare the structure of the aqueous A (25-35) peptide studied here to that of other amyloid peptides. Fonar and Samson (2014) demonstrated by NMR that A (17-34) in water solution adopts an -helical structure for the residues 19-26 and 28-33. Another study on a larger peptide, A (1-40) studied in aqueous environment at pH 7.3 using NMR spectroscopy (Vivekanandan et al, 2011) showed that the peptide adopts a stable -helical structure in the central hydrophobic core and contacts of the N-and C-termini with the central -helix.…”
Section: Discussionmentioning
confidence: 99%